Pembuatan Akta Wasiat oleh Warga Negara Asing di Indonesia Atas Tanah Hak Milik (Studi Putusan MA Nomor 486_K/Pdt/2020) - Kamila, Regina Triana; Sareal, Milly Karmila (Universitas Batanghari Jambi, 2025)
A testamentary grant is a will contains grant of certain items through testament usually made in a form of notarial deed and takes effect after the testator pass away. Many foreign citizens currently carry out legal acts of making testamentary deed in Indonesia and causes conflict to court disputes as in the Supreme Court Decision Number 486_K/Pdt/2020 which concerns a testamentary grant deed made by a foreign citizen on a land which is owned under the name of an Indonesian citizen through Nominee Agreement. The Panel of Judges at all levels have different considerations regarding the validity of the deed. This research aims to determine foreign citizens’ authority in making testamentary deed in Indonesia and the deed’s validity as in the decision being studied. This doctrinal research uses secondary data in the form of legal materials related to Inheritance Law and National Agrarian Law. The research shows that foreign citizens are authorized to make testamentary deeds in Indonesia based on Article 945 of the Civil Code while still complying to Indonesian law. However, a testamentary grant deed made by foreign citizens on land owned by an Indonesian citizen through Nominee Agreement is null and void and the deed is invalid due to the violation of National Agrarian Law and the Civil Code.